Symbolism of the Absurd Language in Qasim Finjan’s Plays - Khidr, Ghannam Muhammad; Khaled, Atyaf Talal (Journal of Tikrit University for Humanities, 2020)
Symbol is one of the distinctive features of language. It is one of the most favorite devices for any artist in literature and art as well. The use of symbolism has appeared extensively in different forms of literature. Symbol in its simplest from may be an image or atone of certain connotation in the field of tangible humanitarian experience. The symbol expresses feeling arising from a relationship or interaction with certain components of existence, the creator cannot translate it into language of modesty, when the language is freed from tyranny of its post, the creator has to assign the symbol to what he wants. Literary men are different in their use of the symbol by making that means to penetrate and access to a world that cannot reach the senses, and to express what cannot be conveyed easily to the readers.